Knowledge Level and Frequency of Swimming to the Incidence of Otitis Externa in Swimming Athletes in Medan - Romadhani, Fahmi; Haryuna, Tengku Siti Hajar (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2024)
Highlights: Respondents who had otitis externa and frequently engaged in swimming activities had an adequate level of awareness of the condition. Frequent swimming can cause a person to experience otitis externa.   Abstract Introduction: Otitis externa, also called swimmer's ear, is a common disease in swimmers and poses a significant public health problem. Frequent exposure to water for long periods is very susceptible to infection. This study aimed to ascertain the level of knowledge regarding the connection between otitis externa and swimming and investigate whether there was a correlation between the frequency of swimming and the occurrence of otitis externa. Methods: Using a questionnaire, the sample comprised 74 Tirta Prima Medan Swimming Association members in 2022. Apart from evaluating descriptive comparisons of pretest and post-test knowledge levels, this study also conducted a Spearman rank correlation test to determine the correlation between knowledge level and frequency of swimming with the incidence of otitis externa. The chosen significance level (p) was 0.05. Variables were considered related if the p<0.05 and not considered related if the p>0.05. The International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 26.0 for Windows was used for statistical analysis. Results: Of the 74 study participants, pretest knowledge was categorized as follows: good level of knowledge (6.8%) of respondents, sufficient (58.1%), and (35%) poor. In the post-test assessment, respondents showed good (75.7%), sufficient (21.6%), and poor (2.7%) knowledge. The results of the Spearman analysis test showed a significant correlation (p=0.042) between swimming frequency and the incidence of otitis externa. Meanwhile, there was no significant correlation between the level of knowledge about otitis externa and the incidence of otitis externa, with a p-value of 0.785. Conclusion: The level of knowledge for the pretest was sufficient. For the same respondents, the post-test results showed good knowledge. There was a correlation between swimming frequency and the incidence of otitis externa. However, there was no significant correlation between the level of expertise and the incidence of otitis externa at the Tirta Prima Medan Swimming Association.